2015
DOI: 10.11646/zootaxa.3904.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Annotated Checklist of Chinese Cladocera (Crustacea: Branchiopoda). Part I. Haplopoda, Ctenopoda, Onychopoda and Anomopoda (families Daphniidae, Moinidae, Bosminidae, Ilyocryptidae)

Abstract: Approximately 199 cladoceran species, 5 marine and 194 freshwater and continental saltwater species, live in China. Of these, 89 species are discussed in this paper. They belong to the 4 cladoceran orders, 10 families and 23 genera. There are 2 species in Leptodoridae; 6 species in 4 genera and 3 families in order Onychopoda; 18 species in 7 genera and 2 families in order Ctenopoda; and 63 species in 11 genera and 4 families in non-Radopoda Anomopoda. Five species might be endemic of China and three of Asia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In the eastern Palearctic, D . curvirostris -like specimens have been detected in North China (the exact location is unknown, see 34,59 . However, in the true Asian tropics 60,61 and subtropics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the eastern Palearctic, D . curvirostris -like specimens have been detected in North China (the exact location is unknown, see 34,59 . However, in the true Asian tropics 60,61 and subtropics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…DNA barcoding in the present study also revealed that Daphnia species diversity on the Tibetan Plateau is much higher than previously thought (Chiang, ; Chiang & Chen, ; Chiang & Du, ; Chiang et al., ; Shen & Sung, ), doubling the described and provisional species number from 5 ( D. magna , D. tibetana , D. pulex , D. similoides , and D. dentifera ) to 10. Recently, an updated checklist of Chinese Cladocera was released based on literature analysis and our molecular data (Xiang et al., ). Approximately 19 species of Daphnia are now found in China.…”
Section: Discussionmentioning
confidence: 99%
“…But previous records from China [23,34,[99][100][101][102] need to be checked, as they could belong both to B. zernowi (Amur basin) (i.e. [25,26]) and the SE Asia taxon (at least some populations in southernmost China).…”
Section: Phylogenetics and Phylogeographymentioning
confidence: 99%